Effect of Rotating Speed Fluctuation on External Hydraculic Performance of a Vane Pump - 方坤礼 张玉良 方晓汾 (东华大学学报（英文版）, 2016)
The rotating speed fluctuation for turbomachinery is a common problem, which will cause severe destruction for equipments and basis when the fluctuation is very strong. In this paper,in order to study the transient response characteristics of a radial vane pump subjected to slight（ 5%） and strong（ 20%）fluctuating rotational speeds, the variation characteristics of the external hydraulic performances are numerically predicted by means of computational fluid dynamics（ CFD） technology. The results manifest that the responses of head and flow rate are different relative to the fluctuating characteristics of rotational speed. The response of the former is very satisfied in synchronism,while that of the latter is hysteretic. Meanwhile,it is found that the variation tendencies of the static pressures at the inlet and outlet of the pump are completely opposite, while the response characteristics of the dynamic pressures at the inlet and outlet are nearly identical.Subsequently,in order to further reveal the transient behavior during the instantaneous operating periods,two non-dimensional parameters are employed to deeply analyze it. The result shows that the variation tendencies of these two parameters are also approximately opposite.Moreover,the quasi-steady assumption is not able to be used to accurately assess the transient flow during transient operating periods. The comparison results show that the transient behavior does not show obvious distinctions between slight and strong fluctuating rotating speeds.